The Association Between ASPECTS Score and Dysphagia in Acute Ischemic Stroke Patients - Saragih, Diko Hamonangan; Cut Aria Arina; Nasution, Iskandar (CoinReads Media Prima, 2023)
Introduction: The Alberta Stroke Program Early CT Score (ASPECTS) is a scoring system assessed from CT scans to investigate the involvement of brain regions experiencing early ischemic changes. Lower scores are known to be associated with worse conditions and the occurrence of complications such as dysphagia. This study aimed to assess the relationship between ASPECTS scores and the occurrence of dysphagia in patients with acute ischemic stroke. Method: This cross-sectional analytical study was conducted at RSUP H. Adam Malik Medan from November 2022 to January 2023. ASPECTS scores were assessed based on CT scan results, while dysphagia was evaluated using the GUSS score. The Mann-Whitney U test was performed to assess the relationship between the two variables. Results: : A total of 34 subjects were included in this study. Among them, 11 (32.4%) subjects experienced dysphagia. The median ASPECTS score was 8 (range 3-9). The Mann-Whitney U test showed a significant association between ASPECTS scores and the occurrence of dysphagia (p<0.001). Conclusion: There is a significant relationship between ASPECTS scores and the occurrence of dysphagia.